EEFISIENSI JUMLAH ARMADA BUS PATAS AC ANTAR BEBERAPA PERUSAHAAN BERDASARKAN METODE PERTUKARAN TRAYK DI DKI - Mardiah
Abstrack: The Imbalance of demand and vehicles number of Bus PATAS AC on each route which is the demand is higher than the number of the buses, or the other way, make the efficiency rate of the vehicle use is lower. It occurs to some of the bus operators in DKI Jakarta. The bus route exchange by using the break even is one of the way in determining vehicles number efficiency to cope with demand and load factor of each bus route so that optimal vehicles number could be obtained. In this surve y, there were 31 bus routes of 3 bus operators to be observed comprising 15 routes of PT. PPD, 13 bus routes of PT. Mayasari Bhakti and 3 other routes of PT. Bianglala. The route exchange were done at the whole period permanently or just at certain period temporarily (for example : in the morning, afternoon or evening time) on the route lacking vehicles number to be exchanged by the route with excessive of vehicles number on the same bus terminal origin. At the first stage, the permanently route exchange was done in prior of the temporarily route exchange of one bus operator. On the second stage, the route exchange was conducted between bus operators applying the permanently route exchange in prior of the temporarily route exchange. The parameter used in determination of the optimal result of route exchange was the largest average of Load Factor Break Even (LFBE). From the tweleve origin bus terminals which were analyzed, there were only six terminals which were possible to be applied route exchange that is Kampung Rambutan, Pulogadung, Kota, Blok M, Senen and Kalideres. Besides, there were six bus route which were impossible to do the route exchange due to no other bus route having the same origin terminal. After having the route exchange, it is evaluated that the whole period of the three operators in total at the vehicles condition of A-T showed the decrease of vehicle addition requirement from 167 number of vehicle to 149 vehicle or 11 % decrease, meanwhile the evaluation of the whole period in total at the vehicles condition of A-T & T-A showed the decrease of vehicle addition requirement from 244 number of vehicle to 240 vehicle or 2 % reduction. Difference of the decrease pointed that the decrease of vehicle addition requirement on A-T condition did not certainly cause the decrease of vehicle addition requirement on T-A. The route exchange made the change either of Load Factor Break Even (LFBE) on each route or the largest average of LFBE. Besides, the route exchange affected to decrease of headway on the route receiving vehicles addition. It can occur with the assumption that addition of one vehicle will add one trip. However, the last vehicle on each route still could arrive at the origin terminal before its period time is ended, While the route having the vehicles reduced did not occur decrease of the headway because the vehicle reduction will not lessen the vehicle number on the mentioned route. The vehicle number should be provided by each operator based on A-T vehicle condition are 61 units by PT. Perum PPD, 48 units by PT. Mayasari Bhakti, 39 units by PT. Bianglala. On the other hand, based on AT & T-A vehicle condition, there are 107 units should be provided by PT. Perum PPD, 78 units by PT. Mayasari Bhakti and 55 units PT. Bianglala.